Perkembangan Kerajaan Matan Pada Masa Gusti Muhammad Saunan (Tahun 1922-1942) Ketapang Kalimantan Barat - Rifaldi*, Muhamad; Firmansyah, Haris; Putri, Astrini Eka (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This research aims to find out the history of various periods in several different periods in the Matan Ketapang Kingdom, West Kalimantan, especially in the period 1922-1942, this is an effort to pass on memories to the next generation. This research method itself uses historical research which consists of Topic Selection, Heuristics, Verification, Interpretation, and Historiography. Heuristics or source collection in this research uses oral sources and secondary sources in the form of books related to the Matan Kingdom, both the history of the founding of the Matan Kingdom and how the Matan Kingdom moved from its previous location. Then in the results of this research it was discovered how the arrival of the Dutch and Japanese made people's lives very miserable, where they lived with burdensome "Blasting" taxes. Furthermore, 1922 was the year that Panembahan Gusti Muhammad Saunan was appointed King. During the Panembahan Gusti government, Muhammad Saunan, who was so wise and firm, certainly won the hearts of the people of Ketapang because he never flinched when facing attacks from the invaders. Then, this research also provides knowledge that the last king who ruled in the Matan Ketapang Kingdom, West Kalimantan, namely Gusti Muhammad Saunan, was classified as a modern king because he had educational provisions that could not be underestimated, this he got when he was sent to school at a Dutch school at that time. still a teenager. Until the end of his term of office, due to the foreman tragedy, to be precise, he no longer served as King in 1942 because he was reported to have died and then there was no one left in the Matan Kingdom.